2015
DOI: 10.3389/fpsyg.2015.01220
|View full text |Cite
|
Sign up to set email alerts
|

Associations between musical abilities and precursors of reading in preschool aged children

Abstract: The association between music and language, in particular, the overlap in their processing results in the possibility to use one domain for the enhancement of the other. Especially in the preschool years music may be a valuable tool to train language abilities (e.g., precursors of reading). Therefore, detailed knowledge about associations between musical abilities and precursors of reading can be of great use for designing future music intervention studies that target language-related abilities. Hence, the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 23 publications
4
51
0
3
Order By: Relevance
“…This disagreement between studies may be due to testing different age groups, and points to the need to test at multiple ages with a comprehensive battery of both rhythm (beatbased and nonbeat-based) and reading-related measures. In order to systematically partial out variance associated with different factors and identify specific links between beat-based processing and reading development, measures should address the cognitive, perceptual, and linguistic mechanisms hypothesized to underlie a reading-rhythm relationship, namely: auditory working memory, [51][52][53] attention, 54 sensorimotor integration, 30 processing of precise temporal mechanisms, 1,2,31,55 and generation of predictions based on perceptual regularity. 56 As evident from Table 1, while multiple studies have shown links between rhythm and readingrelated skills, these studies predominantly included rhythm patterns with beat-based structure, thereby excluding the examination of the distinct role of beat-based (versus nonbeat-based) processing in these relations.…”
Section: Research Designs To Explore Links Between Beat-based Processmentioning
confidence: 99%
See 1 more Smart Citation
“…This disagreement between studies may be due to testing different age groups, and points to the need to test at multiple ages with a comprehensive battery of both rhythm (beatbased and nonbeat-based) and reading-related measures. In order to systematically partial out variance associated with different factors and identify specific links between beat-based processing and reading development, measures should address the cognitive, perceptual, and linguistic mechanisms hypothesized to underlie a reading-rhythm relationship, namely: auditory working memory, [51][52][53] attention, 54 sensorimotor integration, 30 processing of precise temporal mechanisms, 1,2,31,55 and generation of predictions based on perceptual regularity. 56 As evident from Table 1, while multiple studies have shown links between rhythm and readingrelated skills, these studies predominantly included rhythm patterns with beat-based structure, thereby excluding the examination of the distinct role of beat-based (versus nonbeat-based) processing in these relations.…”
Section: Research Designs To Explore Links Between Beat-based Processmentioning
confidence: 99%
“…In this paper, we use the terms doi: 10.1111/nyas.13853 Table 1. Summary of child studies on links between rhythm processing and reading-related skills Reference Year N Age (years) PA Reading Rhythm measure Effect size Anvari et al 75 2002 100 4.7, 5.5 Y Y Same/different rhythm discrimination (beat-based patterns, 3-4 beats) 4 years: music (including rhythm)-PA r = 0.59 * , music-reading: r = 0.57 * 5 years: rhythm-PA: r = 0.33 * , rhythm-reading: r = -0.09 Degé et al 51 "beat-based" and "nonbeat-based" to refer to these rhythmic categories. a Beat-based rhythms have distinct psychological properties.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Degé et al (2015) examined the associations between productive and receptive musical abilities and precursors of reading including phonological awareness in 6-year-old preschool children. The results revealed not only significant correlations between productive and perceptive musical abilities with phonological awareness but also associations with further important precursors such as working memory and rapid retrieval of information from long-term memory.…”
Section: Introductionmentioning
confidence: 99%
“…Neste tópico, será apresentado um resumo da pesquisa realizada pelo educador musical e mestre Eder Ricardo da Silva junto ao Programa de Pós-Graduação em Psicologia do Desenvolvimento e Aprendizagem da Universidade Estadual Paulista (UNESP), campus Bauru cujos resultados foram publicados por Silva, Baldin e Santos (2017).Estudos prévios constataram que atividades musicais podem contribuir em diversas áreas do desenvolvimento humano: cognição, linguagem, socialização e raciocínio lógico-matemático (RAUSCHER;ZUPAN, 2000;BRITO, 2003;SCHELLENBERG, 2005;KOELSCH, 2010;DEGÉ;KUBICEK;SCHWARZER, 2015).Dentre estas atividades, há evidências de que o Treino Musical pode favorecer o funcionamento das competências matemáticas de crianças escolares (RIBEIRO; SANTOS, 2017; ARIAS-RODRIGUEZ, 2015). A partir da hipótese de que o treino musical poderia facilitar a aprendizagem da matemática realizamos o primeiro estudo brasileiro sobre o treino musical na Educação Infantil.…”
unclassified